Left ventricular midwall fibrosis as a predictor of sudden cardiac death in non‐ischaemic dilated cardiomyopathy: a meta‐analysis. (30th June 2020) - Wang, Jie; Yang, Fuyao; Wan, Ke; Mui, David; Han, Yuchi; Chen, Yucheng
Abstract: Identification of patients with non‐ischaemic dilated cardiomyopathy (NICM) who are at risk of sudden cardiac death (SCD) and could benefit from an implantable cardioverter defibrillator (ICD) is challenging. The study aims to systematically assess the prognostic value of left ventricular (LV) midwall late gadolinium enhancement (LGE) pattern in patients with NICM and further explore its value on predicting SCD events. The study was prospectively registered in PROPSERO (CRD42019138468). We systematically searched PubMed, Ovid Embase, Cochrane Library, Web of Science, and ClinicalTrials.gov to identify studies that evaluated the association between LV midwall LGE and clinical outcomes (all‐cause mortality, cardiovascular mortality, and SCD or aborted SCD endpoint) in NICM patients. A meta‐analysis was performed to determine pooled odds ratio (OR) for these adverse events. Seven studies including 1827 NICM patients over a mean follow‐up duration of 36.1 ± 19.3 months were included. The presence of LV midwall LGE pattern was observed in 562 (30.8%) patients. The pooled OR was 3.37 [95% confidence intervals (CIs): 1.35–8.42] for all‐cause mortality, 5.56 (95% CI: 1.23–25.22) for cardiovascular mortality, and 2.25 (95% CI: 1.16–3.16) for SCD or aborted SCD. In a subgroup analysis with mean ejection fraction cut‐off point of 35%, the pooled OR for SCD or aborted SCD was 2.06 (95% CI: 1.32–3.22) for LV ejection fraction (LVEF) > 35% and 2.49 (95% CI: 1.48–4.20) for LVEF ≤ 35%. In addition, our study indicated that LV midwall LGE showed an excellent negative predictive value in identifying high‐risk NICM patients and that the number needed to treat with ICD implantation in NICM patients with midwall LGE is 7. The presence of LV midwall on LGE is a significant prognosticator of adverse events in NICM patients. Additionally, patients with LV midwall LGE may be considered for ICD therapy irrespective of LVEF.